Penerapan Metode Resitasi dalam Pembelajaran Tari Zapin Anvaya pada Kegiatan Ekstrakurikuler di Sanggar Xavitri SMP Xaverius 3 Palembang: Penelitian - Salsabilla Anggia; Efita Elvandari; Dedy Firmansyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study discusses the use of the recitation method in learning Zapin Anvaya dance in extracurricular activities at SMP Xaverius 3 Palembang. The recitation method learning model used in learning Zapin Anvaya dance is the main focus of this study. The research method used in this study is Pre-Experimental Design, especially One-Group Pretest-Posttest Design. A total of 15 children who participated in extracurricular activities were used as the population and sample of this study. Practical tests and t-tests were used as testing methods in data collection and processing. Based on the results of the researcher's research, the average pre-test score of students was 62.3 and the average post-test score of students was 96. After obtaining the results of the student test, the researcher used the t-test formula to analyze the data and concluded that t count = 1.27 and t table = 1.20, meaning that t count is greater than t table or (1.27 ≥ 1.20). Thus, H is rejected and H is accepted. Based on the results of the data analysis, it can be said that the Zapin Anvaya dance is taught at SMP Xaverius 3 Palembang using the recitation method.